Dispersant containing copolymer, positive electrode for secondary battery containing said dispersant, and secondary battery containing said positive electrode
Copolymerization of carbon nanomaterials with polymers by copolymerizing dispersants solves the problem of carbon nanomaterials aggregation in the matrix, and improves the resistance of the secondary battery and the low impedance performance of the electrode slurry.
Patent Information
- Application Number
- JP2024542387
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-16
- Filing Date
- 2022-02-21
- Publication Date
- 2025-01-30
AI Technical Summary
The prior art is difficult to effectively disperse carbon nanomaterials, resulting in their aggregation in the matrix, losing their unique mechanical, electrical and thermal properties, and traditional dispersion methods may impair the original properties of carbon materials.
Copolymerization dispersant is used to copolymerize carbon nanomaterials and polymer dispersants through π-π interaction to form copolymerization dispersant, which is used to prepare dispersion solutions and positive electrode slurries of carbon nanomaterials to improve dispersion efficiency.
It realizes efficient dispersion of carbon nanomaterials, maintains its unique characteristics, and improves the resistance of secondary batteries and the low impedance performance of electrode slurry.
Smart Images

Figure 2025502987000001 
Figure 2025502987000002 
Figure 2025502987000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer dispersant, and a dispersion, a positive electrode slurry composition, a positive electrode, and a secondary battery using the same. In particular, the copolymer dispersant can enhance the dispersibility of carbon materials, particularly carbon nanomaterials such as carbon nanotubes, even when used in small amounts. [Background technology]
[0002] Carbon materials have unique mechanical, electrical, and thermal properties, and are therefore used in a variety of fields, including electronics, biotechnology, medicine, etc. Recently, in addition to existing carbon materials such as graphite, activated carbon, and carbon black, carbon nanomaterials such as carbon nanotubes, fullerenes, and graphene have been attracting attention.
[0003] On the other hand, in order to use carbon materials efficiently, the carbon materials must be effectively dispersed in matrices of various materials.
[0004] However, carbon materials, especially carbon nanomaterials, tend to aggregate together within the matrix due to the strong Van der Waals force, which can cause problems such as loss of uniformity and loss of inherent properties.
[0005] Methods for dispersing carbon materials include mechanical dispersion using physical forces such as ultrasonic waves, milling, and high shear force, dispersion using a dispersant, and dispersion by surface modification.
[0006] However, mechanical dispersion and dispersion by surface modification are prone to damage the carbon material, and such damage can significantly reduce the inherent properties of the carbon material (e.g., electrical conductivity, thermal conductivity, etc.).
[0007] Therefore, the dispersion of carbon materials using dispersants is being actively researched. In particular, in order to efficiently disperse carbon nanomaterials such as carbon nanotubes, intensive research is being conducted on wrapping carbon nanomaterials with polymer dispersants and utilizing the π-π interaction between the p orbitals of the aromatic rings of the polymer dispersants and the p orbitals of the carbon nanomaterials.
[0008] However, there are still not many dispersants that can efficiently disperse carbon materials, especially carbon nanomaterials, while maintaining their inherent properties, and there is a demand for research into this. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] U.S. Patent No. 7,655,708 Summary of the Invention [Problem to be solved by the invention]
[0010] Therefore, an object of the present invention is to provide a copolymer dispersant that can efficiently disperse carbon materials (particularly carbon nanomaterials) with only a small amount of use.
[0011] Another object of the present invention is to provide a dispersion using the copolymer dispersant, and a secondary battery using the dispersion to provide an electrode slurry having a high solid content and low resistance.
[0012] However, the problems to be solved by the present application are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0013] In one embodiment of the present application, the following formula 1 is satisfied in a linear sweep voltammetry measurement in which a voltage is applied from 0 V to 6 V at a rate of 0.5 mV / s: A copolymer is provided.
[0014] (Formula 1) 0≦(current value measured at applied voltage 4.2V-current value measured at applied voltage 3V) / (current value measured at applied voltage 3V)≦3
[0015] Another aspect of the present application includes the copolymer, A dispersant is provided.
[0016] Yet another aspect of the present application is a polymerizable composition comprising the copolymer, A solvent, A dispersion is provided.
[0017] Yet another aspect of the present application is a polymerizable composition comprising the copolymer, A positive electrode active material, A slurry composition for a positive electrode is provided.
[0018] Yet another aspect of the present application is a battery comprising: a current collector; a positive electrode active material layer including the copolymer formed on the current collector, Provide the positive electrode.
[0019] Yet another aspect of the present application includes the positive electrode, A secondary battery is provided. Effect of the Invention
[0020] The copolymer according to the present invention has an effect of being able to efficiently disperse carbon materials (particularly carbon nanomaterials) using only a small amount as a dispersant.
[0021] In addition, the dispersion using the dispersant of the present invention can be used in various fields where dispersion of carbon materials is required (e.g., electrodes of batteries and capacitors, etc.), and in particular, can be used in the positive electrode of a secondary battery to improve the performance of the secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention, however, these examples are merely examples of the present invention and do not define the scope of the invention.
[0023] Prior to this, the terms and words used in this specification and claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted with meanings and concepts that correspond to the technical ideas of the present invention, in accordance with the principle that an inventor can appropriately define the concepts of terms in order to explain his / her invention in the best possible way.
[0024] Therefore, it should be understood that the configuration of the embodiment described in this specification is merely one of the most preferred embodiments of the present invention and does not fully represent the technical ideas of the present invention, and that there may be various equivalents and modifications that can replace them at the time of this application.
[0025] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0026] In this specification, the terms "from" and "to" in the expressions "from a to b" and "a~b" that indicate numerical ranges are defined as ≧a and ≦b.
[0027] The copolymer according to one embodiment of the present application can satisfy the following formula 1 in a linear sweep voltammetry measurement in which a voltage is applied from 0 V to 6 V at a rate of 0.5 mV / s.
[0028] (Formula 1) 0≦(current value measured at applied voltage 4.2V-current value measured at applied voltage 3V) / (current value measured at applied voltage 3V)≦3
[0029] If a half cell is manufactured using a copolymer used in lithium secondary batteries as an insulator instead of a separator and lithium as a counter electrode and linear sweep voltammetry is performed, there is a change in current due to lithium metal at about 2 V to 2.5 V, and the current begins to stabilize at 3 V. If a large change in current is measured above 3 V, it can be determined that the copolymer has caused a side reaction, which has a negative effect on the performance of the lithium secondary battery.
[0030] In addition, since the voltage at which the electrolyte begins to decompose is usually 4.3 V, it is difficult to confirm whether the change in current is caused by the copolymer used in the lithium secondary battery at 4.3 V or higher.
[0031] Therefore, the difference in the current values measured at 3 V and 4.2 V can be used to determine the electrochemical stability of the copolymer and its effect on the performance of the lithium secondary battery.
[0032] When a copolymer exceeding the range of the formula 1 is used, the performance of the secondary battery may be deteriorated due to the low electrochemical stability of the copolymer.
[0033] In one embodiment, the copolymer is a copolymer of at least one monomer unit selected from the group consisting of acrylate-based monomer units containing one or more substituted or unsubstituted aromatic rings and vinyl-based monomer units containing one or more substituted or unsubstituted aromatic rings, an acrylate-based monomer unit containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms, and a monomer unit selected from the group consisting of cyano (CN), pyrrolidone (NC4H6O), carboxylic acid (COOH), caprolactam (C5H 10The polar monomer unit may include any one or more selected from the group consisting of CNO), morpholine (C4H8NO), and oxazolidone (C3H4NO2).
[0034] The copolymer contains, based on 100 mol % of the copolymer, 5 mol % or more and 60 mol % or less of any one or more monomer units selected from the group consisting of acrylate-based monomer units containing one or more substituted or unsubstituted aromatic rings and vinyl-based monomer units containing one or more substituted or unsubstituted aromatic rings, 5 mol % or more and 80 mol % or less of the acrylate-based monomer units containing linear or branched aliphatic hydrocarbons having 5 to 22 carbon atoms, and 5 mol % or more and 60 mol % or less of the cyano (CN), pyrrolidone (NC4H6O), carboxylic acid (COOH), caprolactam (C5H 10 The polar monomer unit may include any one or more selected from the group consisting of CNO), morpholine (C4H8NO), and oxazolidone (C3H4NO2).
[0035] In one embodiment, the copolymer may be represented by Formula 1 below:
[0036] [ka]
[0037] In the above Chemical Formula 1, R1~R 12 are the same or different and each independently represents hydrogen or a linear or branched hydrocarbon having 1 to 4 carbon atoms; R'1 is a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms; R' 2 contains one or more substituted or unsubstituted aromatic rings, R'3 is cyano (CN), pyrrolidone (NC4H6O), carboxylic acid (COOH), caprolactam (C5H 10one or more selected from the group consisting of morpholine (C4H8NO) and oxazolidone (C3H4NO2); R'4 contains one or more substituted or unsubstituted aromatic rings; 5 mol%≦l≦80 mol%, 0 mol%≦m≦60 mol%, and 5 mol%≦n≦60 mol%, and 0 mol%≦o≦60 mol%. (However, m and o cannot all be 0 mol%) At least one of m and o in the above Chemical Formula 1 must exceed 0 mol %.
[0038] That is, the monomer unit (1) of the chemical formula 1 corresponds to an acrylate-based monomer unit containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms, the monomer unit (2) of the chemical formula 1 corresponds to an acrylate-based monomer unit containing one or more substituted or unsubstituted aromatic rings, and the monomer unit (3) of the chemical formula 1 corresponds to a cyano (CN), pyrrolidone (NC4H6O), carboxylic acid (COOH), caprolactam (C5H 10 The monomer unit (4) in the formula 1 corresponds to a polar monomer unit containing one or more selected from the group consisting of morpholine (C4H8NO) and oxazolidone (C3H4NO2), and the monomer unit (4) in the formula 1 corresponds to a vinyl monomer unit containing one or more substituted or unsubstituted aromatic rings.
[0039] In one embodiment, R'1 in Chemical Formula 1 is n-pentyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, lauryl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, cetyl, n-hexadecyl, n-heptadecyl, stearyl, n-octadecyl, n-nonadecyl, n-eicosyl, n-heneicosyl, n-docosyl, iso-pentyl, iso-heptyl, may be any one or more selected from the group consisting of isoethyl, isooctyl, isononyl, isodecyl, isoundecyl, isododecyl, isotridecyl, isotetradecyl, isopentadecyl, isocetyl, isohexadecyl, isoheptadecyl, isostearyl, isooctadecyl, isononadecyl, isoeicosyl, isoheneicosyl, and isodocosyl. That is, as the monomer containing R'1, only one type of monomer containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms may be used, or two or more types of monomers containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms may be used together.
[0040] The acrylate monomer containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms may be an acrylate and / or methacrylate containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms, and the acrylate monomer containing one or more substituted or unsubstituted aromatic rings may be an acrylate and / or methacrylate containing one or more substituted or unsubstituted aromatic rings.
[0041] (Meth)acrylate refers to acrylate or methacrylate.
[0042] For example, the acrylate monomer containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms includes n-pentyl(meth)acrylate, n-heptyl(meth)acrylate, n-octyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, n-nonyl(meth)acrylate, and the like. acrylate, n-decyl(meth)acrylate, n-undecyl(meth)acrylate, lauryl(meth)acrylate, n-dodecyl(meth)acrylate, n-tridecyl(meth)acrylate, n-tetradecyl(meth)acrylate th)acrylate, n-pentadecyl(meth)acrylate, cetyl(meth)acrylate, n-hexadecyl(meth)acrylate, n-heptadecyl(meth)acrylate, stearyl(meth)acrylate, n-nonadecyl(meth)acrylate onadecyl(meth)acrylate, n-eicosyl(meth)acrylate, n-heneicosyl(meth)acrylate, n-dococyl(meth)acrylate, iso-pentyl(meth)acrylate, iso-heptyl(meth)acrylate,iso-octyl(meth)acrylate, iso-nonyl(meth)acrylate, iso-decyl(meth)acrylate, iso-undecyl(meth)acrylate, iso-dodecyl(meth)acrylate, iso-tridecyl(meth)acrylate, iso-tetradecyl(meth)acrylate, iso-pentadecyl(meth)acrylate, iso-cetyl(meth)acrylate cetyl(meth)acrylate, iso-hexadecyl(meth)acrylate, iso-heptadecyl(meth)acrylate, iso-stearyl(meth)acrylate, iso-nonadecyl(meth)acrylate, iso-eicosyl(meth)acrylate, iso-heneicosyl(meth)acrylate, iso-docosyl(meth)acrylate, or copolymers thereof, but are not limited thereto.
[0043] The monomer unit containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms can wrap and disperse carbon materials (especially carbon nano materials such as carbon nanotubes) and reduce the viscosity of the dispersion.
[0044] If the linear or branched aliphatic hydrocarbon has less than 5 carbon atoms, it cannot adequately wrap the carbon material (especially carbon nanotubes), resulting in poor dispersion power. If the carbon number exceeds 22, the compatibility with polar solvents such as NMP may be significantly reduced.
[0045] The monomer unit containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms is contained in an amount of 5 mol % to 80 mol % based on the total content of the entire copolymer being 100 mol %.
[0046] If the content of the monomer unit containing the linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms is less than 5 mol%, the particle size and the viscosity of the dispersion liquid will be high, and if it exceeds 80 mol%, the compatibility with polar solvents will decrease and phase separation may occur.
[0047] In one embodiment, R'2 and R'4 in Formula 1 may be the same or different and may each independently include one or more selected from the group consisting of substituted or unsubstituted benzyl, phenyl, phenoxy, naphthalene, anthracene, and pyrene. For example, R'2 may include one or more selected from the group consisting of 3-phenoxybenzyl, σ-phenylphenoxyethyl, biphenylmethyl, 1-naphthyl, 2-naphthyl, 9-anthracenemethyl, and 1-pyrenemethyl, and R'4 may include, but is not limited to, phenyl.
[0048] That is, R'2 and R'4 may be the same or different and each independently contain one or more substituted or unsubstituted aromatic rings.
[0049] Alternatively, R'2 may be a substituted or unsubstituted hydrocarbon containing one or more aromatic rings.
[0050] Furthermore, as the monomer containing R'2, only one type of monomer containing one or more substituted or unsubstituted aromatic rings may be used, or two or more types of monomers containing one or more substituted or unsubstituted aromatic rings may be used together.
[0051] For example, when the aromatic ring is substituted, the substituent may be a linear or branched hydrocarbon having 1 to 4 carbon atoms, a substituent linked via oxygen (O) (for example, a substituted or unsubstituted aromatic ring linked via an ether), or the like.
[0052] In one embodiment, the monomer containing R'2 is selected from the group consisting of benzyl acrylate, 3-phenoxy benzyl acrylate, σ-phenyl phenoxy ethyl acrylate, σ-phenyl phenoxy ethyl methacrylate, (1-pyrene) 2-methyl-2-propenoate, 1-naphthyl acrylate, 1-naphthyl methacrylate, 2-naphthyl acrylate, 2-naphthyl methacrylate, 9-anthracene methyl acrylate, and 9-anthracene methyl methacrylate. The monomer containing R'4 may be any one or more selected from the group consisting of methyl methacrylate, and the monomer containing R'4 may be styrene.
[0053] The monomer unit containing one or more substituted or unsubstituted aromatic rings can act as a dispersant through π-π interactions with carbon materials (especially carbon nanomaterials such as carbon nanotubes) and can be compatible with polar solvents such as NMP.
[0054] The monomer unit containing one or more substituted or unsubstituted aromatic rings is contained in an amount of 5 to 60 mol % based on 100 mol % of the total content of the entire copolymer.
[0055] If the content of the monomer units containing one or more substituted or unsubstituted aromatic rings exceeds 60 mol%, the contents of aliphatic hydrocarbons and polar monomer units are reduced, which may increase the viscosity of the dispersion and increase the particle size of the dispersed carbon material.
[0056] The above cyano (CN), pyrrolidone (NC4H6O), carboxylic acid (COOH), caprolactam (C5H 10 The polar monomer units, including any one or more selected from the group consisting of CNO), morpholine (C4H8NO) and oxazolidone (C3H4NO2), can play a role in imparting compatibility with polar solvents such as NMP.
[0057] For example, the cyano (CN), pyrrolidone (NC4H6O), carboxylic acid (COOH), caprolactam (C5H 10 The polar monomer including any one or more selected from the group consisting of N-vinylpyrrolidone, N-vinylcaprolactam, 4-acryloylmorpholine, 3-acryloyl-2-oxazolidinone, or a copolymer thereof may be used.
[0058] The polar monomer unit is contained in an amount of 5 to 60 mol % based on 100 mol % of the total content of the entire copolymer.
[0059] If the polar monomer unit is more than 60 mol % of the total copolymer, the compatibility with the polar solvent may be excessively high, resulting in phase separation after dispersion and increasing the particle size of the dispersed carbon material.
[0060] In one embodiment, the copolymer may be a random or block copolymer depending on the synthetic process.
[0061] In one embodiment, the copolymer may have a number average molecular weight of 8,000 or more and 40,000 or less.
[0062] If the number average molecular weight of the copolymer is less than 8,000, the fluidity of the dispersant increases and the ability to prevent re-agglomeration of the carbon material decreases, and if the number average molecular weight exceeds 40,000, the viscosity may be too high for use.
[0063] A dispersant according to another aspect of the present application may contain the copolymer.
[0064] A dispersion according to yet another aspect of the present application may include the copolymer and a solvent.
[0065] In one embodiment, the solvent may be a polar solvent, for example, any one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), dimethylformamide (DMF), dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), γ-butyrolactone, ethyl acetate, propyl acetate, ethanol, isopropyl alcohol, and deionized water.
[0066] In one embodiment, the dispersion liquid may further include a carbon material, which may be, but is not limited to, any one or more selected from the group consisting of graphite, activated carbon, carbon black, carbon nanotubes, fullerenes, and graphene.
[0067] The carbon nanotubes may be single-walled carbon nanotubes, multi-walled carbon nanotubes, or a combination thereof.
[0068] On the other hand, in the dispersion liquid, the content of the dispersant may be 0.1 to 0.5 times the content of the carbon material.
[0069] If the content of the dispersant is less than 0.1 times the content of the carbon material, a sufficient dispersion effect cannot be obtained, and the carbon material cannot be efficiently dispersed.
[0070] In addition, if the content of the dispersant is more than 0.5 times that of the carbon material, the ratio of the secondary material in the battery increases, which may reduce the energy density.
[0071] The copolymer dispersant of the present invention has excellent dispersing power and can produce a dispersion of carbon materials (particularly carbon nanotubes) having uniform and dense particle size.
[0072] On the other hand, the carbon material (particularly, carbon nanotubes) is contained in an amount of 1 to 10% by weight based on 100% by weight of the dispersion liquid.
[0073] If the content of the carbon material in the dispersion is less than 1 wt%, the solid content of the electrode slurry will be low, and if it exceeds 10 wt%, the viscosity will be too high and dispersion will not be performed well, making it difficult to produce a good quality dispersion.
[0074] The copolymer dispersant of the present invention has excellent dispersing power, which not only reduces the particle size of carbon nanotubes in the dispersion and lowers the viscosity of the dispersion, but also shortens the dispersion process time.
[0075] In one embodiment, when the dispersion contains 1.5 wt% solids, the viscosity of the dispersion at a shear rate of 10 / s may be 2,000 cps or less, and the average particle size (D50) of the single-walled carbon nanotubes, the multi-walled carbon nanotubes, or a combination thereof dispersed in the dispersion may be 6 μm or less.
[0076] A positive electrode slurry composition according to still another aspect of the present application may include the copolymer and a positive electrode active material.
[0077] The positive electrode slurry composition contains the carbon nanotubes in an amount of 0.001 to 0.1 times, and preferably 0.003 to 0.02 times, the content of the positive electrode active material.
[0078] If the carbon nanotube content is less than 0.001 times the positive electrode active material content, the conductivity in the electrode active material will decrease, resulting in a decrease in output characteristics. If the carbon nanotube content is more than 0.1 times the positive electrode active material content, the positive electrode active material content will be too low, resulting in a decrease in capacity.
[0079] The positive electrode active material used in the present invention can be any positive electrode active material available in the art. Specific examples of such positive electrode active materials include lithium metal; lithium cobalt-based oxides such as LiCoO2; Li 1+x Mn 2-x O4 (where x is 0 to 0.33), lithium manganese-based oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxides such as Li2CuO2; vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; LiNi 1-x M x O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga and x = 0.01 to 0.3), lithium nickel-based oxides represented by; LiMn 2-x M x O2 (where M = Co, Ni, Fe, Cr, Zn or Ta and x = 0.01 to 0.1) or lithium manganese composite oxides represented by Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); Li(Ni a Co b Mn c )O2 (where 0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), lithium-nickel-manganese-cobalt-based oxides; sulfur or disulfide compounds; phosphates such as LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4; Fe2(MoO4)3, etc. can be mentioned, but it is not limited to only these.
[0080] At this time, the positive electrode active material layer can additionally contain a binder, a conductive material, a filler, and other additives in addition to the positive electrode active material.
[0081] The positive electrode active material is contained in an amount of 90 to 99% by weight based on the solid content. If the content of the active material is low, the battery cannot achieve a high capacity. If the content of the active material is excessively high, the contents of the binder, conductive material, etc. will be relatively reduced, so the electrode adhesion, conductivity, etc. may decrease.
[0082] The conductive material is not particularly limited and can be appropriately selected depending on the type of battery and capacitor. For example, in the case of a lithium ion secondary battery, carbon such as graphite or activated carbon is used, and in the case of a nickel-hydrogen secondary battery, cobalt oxide is used for the negative electrode, and nickel powder, cobalt oxide, titanium oxide, carbon, etc. are used for the negative electrode.
[0083] Examples of the carbon include acetylene black, furnace black, graphite, carbon fiber, and fullerenes.
[0084] The amount of the conductive material used is usually 1 to 20 parts by weight, and preferably 2 to 10 parts by weight, based on 100 parts by weight of the electrode active material.
[0085] The energy density of the secondary battery can be improved by decreasing the content of the conductive material and increasing the content of the positive electrode active material, so it is important to achieve high efficiency even when the same amount of conductive material is used.
[0086] The smaller and more uniformly dispersed the conductive material used in the secondary battery electrode slurry is, the higher the conductive efficiency will be, which will reduce the resistance inside the battery and improve the output characteristics and life characteristics. If the conductive material is large and unevenly dispersed, even if the same amount is used, the binding characteristics and conductivity will be reduced, which will have a negative effect on the life and output characteristics of the battery. In addition, if the viscosity of the dispersion is low, the solid content of the slurry can be increased to improve the production speed of the electrode.
[0087] Examples of binders for secondary battery positive electrodes include, but are not limited to, one or more of the following: poly(meth)acrylic acid, poly(meth)acrylamide, carboxymethyl cellulose, polyvinylidene fluoride, polyhexafluoropropylene-polyvinylidene fluoride copolymer (P(VdF / HFP)), poly(vinyl acetate), polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, alkylated polyethylene oxide, polyvinyl ether, poly(methyl methacrylate), poly(ethyl acrylate), polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, styrene-butadiene rubber, acrylonitrile-butadiene rubber, and copolymers thereof.
[0088] The content of the binder in the positive electrode slurry composition is preferably 0.3 wt% to 10 wt%, more preferably 0.7 wt% to 8 wt%, calculated on a solid content basis. If the content is less than 0.3 wt%, it is difficult to expect sufficient binding strength between the current collector and the electrode composition, and if the content exceeds 10 wt%, the ratio of the binder in the electrode slurry composition increases, which may reduce the battery capacity.
[0089] A positive electrode according to yet another aspect of the present application may include a current collector and a positive electrode active material layer including the copolymer of the present application formed on the current collector.
[0090] The positive electrode can be manufactured by (a) preparing a composition for forming a positive electrode active material layer, the composition including a positive electrode active material and the copolymer of the present application, and (b) applying the composition for forming a positive electrode active material layer onto a positive electrode current collector, followed by drying.
[0091] The positive electrode active material layer forming composition can be mixed by a conventional mixer, such as a high-speed shear mixer or a homogenizer, in a conventional manner.
[0092] The step (b) is a step of coating the composition for forming a positive electrode active material layer prepared in the step (a) on a positive electrode current collector, and then drying the composition to produce a positive electrode for a lithium secondary battery.
[0093] In this regard, the method of applying the slurry-like composition for forming a positive electrode active material layer is not limited, and for example, the composition may be prepared by a doctor blade coating, a dip coating, a gravure coating, a slit die coating, a spin coating, a comma coating, a bar coating, a reverse roll coating, a screen coating, a cap coating, or the like.
[0094] After coating, the coating is dried, and finally, a positive electrode for a secondary battery (particularly a lithium secondary battery) having a positive electrode active material layer formed thereon can be produced.
[0095] The current collector can be any material that is conductive and does not chemically react with the electrode-forming slurry. Typical examples are aluminum foil and copper foil. A current collector having a thickness of 3 to 50 micrometers can be selected and used.
[0096] A secondary battery according to still another aspect of the present application may include the positive electrode.
[0097] The secondary battery of the present application may have an AC resistance of 30Ω or less, a capacity retention rate of 80% or more when charged and discharged 300 times, an average charging voltage of 3.75V or less, and an average discharging voltage of 3.73V or more.
[0098] A secondary battery can be produced that comprises a positive electrode, a negative electrode, a separator, and an electrolyte solution that contain the copolymer of the present invention.
[0099] The separator must be an insulator that can separate the negative and positive electrodes, and must provide a path through which only lithium ions can move. To achieve this, it must have good wettability with the electrolyte, and porous polymer films such as PE / PP or porous nonwoven fabrics are used. To prevent short circuits in the battery, coated separators coated with ceramics that have enhanced heat resistance and mechanical strength can be used, and are coated in single or multiple layers.
[0100] The separator is made of a porous substrate. The porous substrate may be any porous substrate typically used in electrochemical devices, such as, but not limited to, a polyolefin-based porous membrane or nonwoven fabric.
[0101] The separation membrane may be a porous substrate made of any one selected from the group consisting of polyethylene, polypropylene, polybutylene, polypentene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalate, or a mixture of two or more of these.
[0102] The electrolyte of the lithium secondary battery is a non-aqueous electrolyte containing a lithium salt, and is composed of a lithium salt and a solvent. The solvent may be a non-aqueous organic solvent, an organic solid electrolyte, or an inorganic solid electrolyte.
[0103] The lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte solution, and examples of the lithium salt include LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiC4BO8, LiCF3CO2, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2F)2, LiN(SO2C2F5)2, LiC4F9SO3, LiC(CF3SO2)3, (CF3SO2)·2NLi, lithium chloroborane, lithium lower aliphatic carboxylates, and lithium 4-phenylborate imide can be used.
[0104] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, tetrahydroxyfuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, 4-methyl-1,3-dioxene, diethyl ether, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0105] Examples of the organic solid electrolyte that can be used include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing secondary dissociation groups.
[0106] Examples of the inorganic solid electrolyte that can be used include nitrides, halides, and sulfates of Li, such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0107] The non-aqueous electrolyte may further contain other additives for the purpose of improving charge / discharge characteristics, flame retardancy, etc. Examples of the additives include pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, fluoroethylene carbonate (FEC), propene sultone (PRS), vinylene carbonate (VC), etc.
[0108] The lithium secondary battery according to the present invention can be manufactured by lamination stacking of separators and electrodes and folding processes in addition to the general winding process, and the battery case may be cylindrical, square, pouch-shaped, or coin-shaped.
[0109] The lithium secondary battery using the dispersion liquid of the present invention, in which small and uniformly dispersed carbon nanotubes are used, can improve the capacity retention rate and life characteristics. Furthermore, such a lithium secondary battery can be used in small to medium-sized models such as automobiles and electronic devices. EXAMPLES
[0110] The present application will be described in more detail below using examples, but the present application is not limited thereto.
[0111] [Example 1-1] Into a five-neck flask reactor, 42 g of 3-phenoxy benzyl acrylate (PBA), 52 g of stearyl acrylate (SA), 6 g of acrylic acid (AA), and 70 g of N-methyl pyrrolidone (NMP) were placed, and after attaching a reflux condenser and a thermometer, the mixture was purged with nitrogen and heated to 75°C.
[0112] Next, 0.15 g of 2,2'-azobis-2,4-dimethyl valeronitrile (V-65) was dissolved in 20 g of N-methylpyrrolidone, and the solution was added dropwise for 30 minutes.
[0113] After the completion of the dropping, the temperature was kept at 75°C for 7 hours, and 0.15 g of V-65 dissolved in 10 g of N-methylpyrrolidone was added dropwise for 30 minutes, and the temperature was kept at 75°C for 7 hours to synthesize a dispersant with a solid content of 50% and a number average molecular weight of about 14,000 g / mol.
[0114] [Example 1-2] The synthesis was carried out in the same manner as in Example 1-1, except that the reaction temperature was lowered to 70° C. and the number average molecular weight was adjusted to about 20,000.
[0115] [Examples 1-3] The synthesis was carried out in the same manner as in Example 1-1, except that the reaction temperature was lowered to 65° C. and the number average molecular weight was adjusted to about 32,000.
[0116] [Examples 1-4] The synthesis was carried out in the same manner as in Example 1-1, except that 42 g of 3-phenoxybenzyl acrylate, 52 g of stearyl acrylate, and 6 g of acrylic acid were used as monomers, and instead, 60 g of stearyl acrylate, 26 g of styrene, and 14 g of acrylic acid were used.
[0117] [Examples 1-5] The synthesis was carried out in the same manner as in Example 1-1, except that 46 g of 3-phenoxybenzyl acrylate, 46 g of lauryl acrylate (LA), and 8 g of acrylic acid were used instead of 42 g of 3-phenoxybenzyl acrylate, 52 g of stearyl acrylate, and 6 g of acrylic acid as monomers.
[0118] [Comparative Example 1-1] The synthesis was carried out in the same manner as in Example 1-1, except that the reaction temperature was raised to 85° C. and the number average molecular weight was adjusted to about 5,000.
[0119] [Comparative Example 1-2] The synthesis was carried out in the same manner as in Example 1-1, except that the reaction temperature was lowered to 65° C., and 0.05 g of 2,2′-azobis-2,4-dimethylvaleronitrile was added twice to adjust the number average molecular weight to about 50,000.
[0120] [Comparative Example 1-3] The synthesis was carried out in the same manner as in Example 1-1, except that 70 g of 3-phenoxybenzyl acrylate and 30 g of acrylic acid were used instead of 42 g of 3-phenoxybenzyl acrylate, 52 g of stearyl acrylate and 6 g of acrylic acid.
[0121] [Comparative Example 1-4] The synthesis was carried out in the same manner as in Example 1-1, except that 45 g of 3-phenoxybenzyl acrylate, 50 g of butyl acrylate (BA), and 5 g of acrylic acid were used instead of 42 g of 3-phenoxybenzyl acrylate, 52 g of stearyl acrylate, and 6 g of acrylic acid.
[0122] The compositions, composition ratios, and reaction conditions of Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-4 are shown in Table 1 below.
[0123] [Table 1]
[0124] In Table 1, PBA stands for 3-phenoxy benzyl acrylate, SM stands for styrene, SA stands for stearyl acrylate, BA stands for butyl acrylate, LA stands for lauryl acrylate, AA stands for acrylic acid, V-65 stands for 2,2'-azobis-2,4-dimethyl valeronitrile, and NMP stands for N-methyl pyrrolidone.
[0125] The molecular weights and electrochemical stability of the copolymers produced in Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-4 were measured, and the molecular weights are shown in Table 2 below.
[0126] The molecular weights of the conventional dispersants H-NBR (hydrogenated nitrile rubber) and PVP (polyvinylpyrrolidone) used in the preparation of the comparative dispersion are also shown in Table 2 below.
[0127] The molecular weight of the prepared copolymer was measured by gel permeation chromatography (GPC) using THF as a solvent.
[0128] In addition, the electrochemical stability of the prepared copolymer was measured by Linear Sweep Voltammetry (LSV) measurement method using a Biologic electrochemical device from 0 V to 6 V at a rate of 0.5 mV / s.
[0129] It was confirmed that all of the copolymers of Examples 1-1 to 1-5 were within the range of the following formula 1 and had excellent electrochemical stability.
[0130] (Formula 1) 0≦(current value measured at applied voltage 4.2V-current value measured at applied voltage 3V) / (current value measured at applied voltage 3V)≦3
[0131] [Table 2]
[0132] [Example 2-1] 0.26 g of the copolymer prepared in Example 1-1 as a dispersant, 1.24 g of multi-walled carbon nanotubes (average diameter 10 nm, length 150 μm), 98.5 g of N-methyl pyrrolidone, and 200 g of 0.65 mm zirconia beads were put into a planetary ball mill and dispersed at 400 rpm for 30 minutes to prepare a dispersion with a solid content of 1.5%.
[0133] [Example 2-2] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Example 1-2 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0134] [Example 2-3] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Example 1-3 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0135] [Example 2-4] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Example 1-4 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0136] [Example 2-5] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Example 1-5 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0137] [Comparative Example 2-1] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Comparative Example 1-1 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0138] [Comparative Example 2-2] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Comparative Example 1-2 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0139] [Comparative Example 2-3] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Comparative Example 1-3 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0140] [Comparative Example 2-4] A dispersion was prepared in the same manner as in Example 2-1, except that the copolymer prepared in Comparative Example 1-4 was used as the dispersant instead of the copolymer prepared in Example 1-1.
[0141] [Comparative Example 2-5] A dispersion was prepared in the same manner as in Example 2-1, except that hydrogenated-nitrile butadiene rubber (H-NBR) having a number average molecular weight of 70,000 was used as the dispersant, instead of the copolymer prepared in Example 1-1.
[0142] [Comparative Example 2-6] A dispersion was prepared in the same manner as in Example 2-1, except that beads with a diameter of 2 mm were used instead of the zirconia beads with a diameter of 0.65 mm.
[0143] [Comparative Example 2-7] A dispersion was prepared in the same manner as in Example 2-1, except that polyvinylpyrrolidone (PVP) having a number average molecular weight of 40,000 was used as the dispersant, instead of the copolymer prepared in Example 1-1.
[0144] The measured physical properties of the dispersions of Examples 2-1 to 2-5 and Comparative Examples 2-1 to 2-7 are shown in Table 3 below.
[0145] The viscosity of the prepared dispersion was measured by a Haake Mars rheometer, and the particle size was measured by a Mastersizer 3000. The particle size of the dispersion corresponds to the value at D50, and the viscosity of the dispersion corresponds to the value at a shear rate of 10 / s.
[0146] The dispersions of Examples 2-1 to 2-5 had lower measured viscosities than the dispersions of Comparative Examples 2-2 to 2-5 and 2-7. Also, the dispersions of Examples 2-1 to 2-5 had smaller measured carbon nanotube particle sizes than the dispersions of Comparative Examples 2-3 and 2-5 to 2-7.
[0147] This shows that the copolymers used in the dispersions of Examples 2-1 to 2-5 have relatively superior carbon nanotube dispersing performance compared to the copolymers or homopolymers used in the dispersions of Comparative Examples 2-2 to 2-7.
[0148] In addition, it was confirmed that the characteristics of the dispersion liquid can be changed according to the process conditions of the dispersion liquid preparation step, as in Comparative Example 2-6.
[0149] In particular, by comparing the viscosity and particle size of the dispersions of Comparative Examples 2-1 to 2-4, in which copolymers different only in number average molecular weight from the copolymers used in the dispersions of Examples 2-1 to 2-5 were used, it was confirmed that adjusting the number average molecular weight of the copolymer to approximately 8,000 to 40,000 g / mol is preferable for producing a carbon nanotube dispersion.
[0150] [Table 3]
[0151] [Example 3-1] 14 g of the dispersion of Example 2-1, 20 g of a positive electrode active material (NCM622), 8 g of PVdF dissolved in N-methyl pyrrolidone at 8 wt%, and 4 g of N-methyl pyrrolidone were mixed in a planetary centrifugal mixer (ARE-310, Thinky) to prepare a slurry for forming a positive electrode, and the solid content of the slurry was 50%.
[0152] The slurry was applied to an aluminum foil having a thickness of 20 μm using a comma coater. The electrode to which the slurry was applied was dried in an oven at 130° C. for 12 hours or more, and then rolled to adjust the mixture density to 2.4 g / cc. Then, the electrode was vacuum dried at 110° C. to prepare a positive electrode plate.
[0153] A 2032 coin half cell was manufactured using the positive electrode plate as the positive electrode and lithium metal as the negative electrode, and the AC-IR (alternating current resistance) was evaluated using a Biologic electrochemical device. A 2032 coin full cell was manufactured using the graphite / silicon plate as the negative electrode, and the charge / discharge voltage characteristics and life characteristics were evaluated.
[0154] [Example 3-2] A positive electrode plate, a coin half cell, and a coin full cell were manufactured in the same manner as in Example 3-1, except that a slurry for forming a positive electrode was manufactured using 11.2 g of the dispersion of Example 2-1, 19.82 g of a positive electrode active material (NCM622), 10.48 g of PVdF dissolved in N-methyl pyrrolidone at 8 wt%, and 4 g of N-methyl pyrrolidone in a planetary centrifugal mixer (ARE-310, Thinky), and the characteristics were evaluated.
[0155] [Example 3-3] A positive electrode plate, a coin half cell, and a coin full cell were manufactured in the same manner as in Example 3-1, except that a slurry for forming a positive electrode was manufactured using 9.8 g of the dispersion of Example 2-1, 19.82 g of a positive electrode active material (NCM622), 10.48 g of PVdF dissolved in N-methyl pyrrolidone at 8 wt%, and 4 g of N-methyl pyrrolidone in a planetary centrifugal mixer (ARE-310, Thinky), and the characteristics were evaluated.
[0156] [Comparative Example 3-1] A positive electrode plate, a coin half cell, and a coin full cell were manufactured in the same manner as in Example 3-1, except that the dispersion liquid of Comparative Example 2-5 was used instead of the dispersion liquid of Example 2-1, and the characteristics were evaluated.
[0157] [Comparative Example 3-2] A positive electrode plate, a coin half cell, and a coin full cell were produced in the same manner as in Example 3-1, except that the dispersion liquid of Comparative Example 2-6 was used instead of the dispersion liquid of Example 2-1, and the characteristics were evaluated.
[0158] The compositions and characteristics of the positive electrode slurries used in Examples 3-1 to 3-3 and Comparative Examples 3-1 and 3-2 are shown in Table 4 below.
[0159] The viscosity of the produced slurry was measured using a Haake Mars rheometer, and the viscosity of the slurry corresponds to the value at a shear rate of 10 / s.
[0160] [Table 4]
[0161] From the measurement results in Table 4, it was confirmed that the lower the viscosity of the dispersion, the lower the viscosity of the positive electrode slurry.
[0162] The performance of the batteries produced in Examples 3-1 to 3-3 and Comparative Examples 3-1 and 3-2 is shown in Table 5 below.
[0163] [Table 5]
[0164] In Table 5, the lower the AC-IR value, the lower the resistance of the electrode, which means improved output characteristics.
[0165] The output characteristics can be determined from the average voltage during charging and the average voltage during discharging. If the voltage during charging is low, less energy is consumed when charging, and if the voltage during discharging is high, more energy can be output when charged with the same capacity.
[0166] As a result of evaluating the performance of the secondary batteries of Examples 3-1 to 3-3 produced using the dispersion of Example 2-1, it can be confirmed that when the resistance value is low, the average charge voltage is low and the average discharge voltage is high.
[0167] Furthermore, from the evaluation of the secondary battery performance of Examples 3-1 to 3-3 in which the amount of the dispersion liquid of Example 2-1 used in the positive electrode slurry was adjusted, it was confirmed that not only was the resistance low but the capacity retention rate was high even when the amount of carbon nanotubes used was reduced.
[0168] It has been confirmed that the dispersion using the copolymer of the present application has excellent dispersion properties for carbon materials due to an appropriate balance of viscosity and carbon nanotube particle size, and thus can improve the performance of secondary batteries even when used in relatively small amounts.
[0169] The scope of the present invention is indicated by the claims set forth below rather than by the above detailed description, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be interpreted as being included in the scope of the present invention. [Industrial Applicability]
[0170] The copolymer according to the present invention has an effect of being able to efficiently disperse carbon materials (particularly carbon nanomaterials) using only a small amount as a dispersant.
[0171] In addition, the dispersion using the dispersant of the present invention can be used in various fields where dispersion of carbon materials is required (e.g., electrodes of batteries and capacitors, etc.), and in particular, can be used in the positive electrode of a secondary battery to improve the performance of the secondary battery.
Claims
1. In a linear sweep voltammetry measurement in which a voltage is applied from 0 V to 6 V at a rate of 0.5 mV / s, the following formula 1 is satisfied: Copolymer. (Formula 1) 0≦(current value measured at applied voltage of 4.2 V−current value measured at applied voltage of 3 V) / (current value measured at applied voltage of 3 V)≦3
2. one or more monomer units selected from the group consisting of acrylate-based monomer units containing one or more substituted or unsubstituted aromatic rings, and vinyl-based monomer units containing one or more substituted or unsubstituted aromatic rings; an acrylate-based monomer unit containing a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms; and Cyano (CN), pyrrolidone (NC 4 H 6 O), carboxylic acid (COOH), caprolactam (C 5 H 10 CNO), morpholine (C 4 H 8 NO) and oxazolidones (C 3 H 4 NO 2 a polar monomer unit including at least one selected from the group consisting of The copolymer of claim 1.
3. one or more monomer units selected from the group consisting of acrylate-based monomer units containing one or more substituted or unsubstituted aromatic rings and vinyl-based monomer units containing one or more substituted or unsubstituted aromatic rings, the amount of which is 5 mol % or more and 60 mol % or less, based on 100 mol % of the copolymer; an acrylate-based monomer unit containing 5 mol % or more and 80 mol % or less of the linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms; and 5 mol % or more and 60 mol % or less of the above cyano (CN), pyrrolidone (NC 4 H 6 O), carboxylic acid (COOH), caprolactam (C 5 H 10 CNO), morpholine (C 4 H 8 NO) and oxazolidones (C 3 H 4 NO 2 The polar monomer unit includes at least one selected from the group consisting of The copolymer of claim 1.
4. Represented by the following chemical formula 1: The copolymer of claim 1. 【Chemistry 1】 In the above Chemical Formula 1, R 1 ~R 12 are the same or different and each independently represents hydrogen or a linear or branched hydrocarbon having 1 to 4 carbon atoms; R' 1 is a linear or branched aliphatic hydrocarbon having 5 to 22 carbon atoms; R' 2 contains one or more substituted or unsubstituted aromatic rings, R' 3 Cyano (CN), pyrrolidone (NC 4 H 6 O), carboxylic acid (COOH), caprolactam (C 5 H 10 CNO), morpholine (C 4 H 8 NO) and oxazolidones (C 3 H 4 NO 2 ) any one or more selected from the group consisting of R' 4 contains one or more substituted or unsubstituted aromatic rings, 5 mol%≦l≦80 mol%, 0 mol%≦m≦60 mol%, and 5 mol%≦n≦60 mol%, and 0 mol%≦o≦60 mol%. (However, all of m and o cannot be 0 mol %)
5. R' 1 is n-pentyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, lauryl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, cetyl, n-hexadecyl, n-heptadecyl, stearyl, n-octadecyl, n-nonadecyl, n-eicosyl, n-heneicosyl, n-docosyl, iso-pentyl, iso-heptyl, iso-octyl, including any one or more selected from the group consisting of octyl, iso-nonyl, iso-decyl, iso-undecyl, iso-dodecyl, iso-tridecyl, iso-tetradecyl, iso-pentadecyl, iso-cetyl, iso-hexadecyl, iso-heptadecyl, iso-stearyl, iso-octadecyl, iso-nonadecyl, iso-eicosyl, iso-heneicosyl, and iso-docosyl; The copolymer according to claim 4.
6. R' 2 and R' 4 are the same or different, and each independently includes one or more selected from the group consisting of substituted or unsubstituted benzyl, phenyl, phenoxy, naphthalene, anthracene, and pyrene; The copolymer according to claim 4.
7. R' 2 includes at least one selected from the group consisting of 3-phenoxybenzyl, σ-phenylphenoxyethyl, biphenylmethyl, 1-naphthyl, 2-naphthyl, 9-anthracenemethyl, and 1-pyrenemethyl; R' 4 contains phenyl, The copolymer according to claim 4.
8. R' 2 The monomers containing the above are benzyl acrylate, 3-phenoxybenzyl acrylate, σ-phenylphenoxyethyl acrylate, σ-phenylphenoxyethyl methacrylate, (1-pyrene) 2-methyl-2-propenoate, 1-naphthyl acrylate, 1-naphthyl methacrylate, and the like. methacrylate), 2-naphthyl acrylate, 2-naphthyl methacrylate, 9-anthracene methyl acrylate, and 9-anthracene methyl methacrylate; R' 4 The monomer containing is styrene. The copolymer according to claim 4.
9. The copolymer is a random or block copolymer. The copolymer of claim 1.
10. The number average molecular weight of the copolymer is 8,000 or more and 40,000 or less. The copolymer of claim 1.
11. The copolymer according to any one of claims 1 to 10, Dispersant.
12. The copolymer according to any one of claims 1 to 10, A solvent, dispersion liquid.
13. The solvents include N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), dimethylformamide (DMF), dimethylacetamide (DMAc), dimethylsulfoxide (DMSO), γ-butyrolactone, ethyl acetate, propyl acetate, ethanol, isopropyl alcohol, and water (deionized water). water), 13. The dispersion of claim 12.
14. It additionally contains a carbon material.
13. The dispersion of claim 12.
15. The carbon material is at least one selected from the group consisting of graphite, activated carbon, carbon black, single-walled carbon nanotubes, multi-walled carbon nanotubes, fullerenes, and graphenes.
15. The dispersion of claim 14.
16. When the dispersion contains 1.5 wt % solids, the viscosity of the dispersion at a shear rate of 10 / s is 2,000 cps or less; The average particle size (D50) of the single-walled carbon nanotubes, the multi-walled carbon nanotubes, or a combination thereof dispersed in the dispersion liquid is 6 μm or less.
16. The dispersion of claim 15.
17. The copolymer according to any one of claims 1 to 10, A positive electrode active material, A slurry composition for a positive electrode.
18. A current collector; A positive electrode active material layer comprising the copolymer according to any one of claims 1 to 10 formed on the current collector. Positive electrode.
19. 19. The positive electrode of claim 18, Secondary battery.
Citation Information
Patent Citations
Coating composition for precoated metal and precoated metal plate
JP1999263934A
polymer composition
JP1999501690A
Electrochemical sensing using enzyme electrodes
JP2005531764A
Ink recording material, recording method and recording device
JP2010105364A
Pigment composition and production method of the same, and inkjet ink
JP2016199653A